2020
DOI: 10.1039/d0cp03579c
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-induced ionic to mixed ionic and electronic conduction transition in solid electrolyte LaF3

Abstract: The ionic transport properties of solid electrolyte LaF3 was systematically studied under high pressures up to 30.6 GPa with alternate-current impedance spectra measurements and first-principles calculations. From impedance spectra measurements,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…23 Parallel plate electrodes were fabricated on the DAC to measure the impedance spectrum. 18 We used two thin platinum foils as the electrodes and attached them to the top and bottom of the sample. And a layer of a mixture of Al 2 O 3 and epoxy was applied to insulate the electrode from the gasket (as shown in Fig.…”
Section: Raman Spectroscopy and Impedance Spectroscopic Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Parallel plate electrodes were fabricated on the DAC to measure the impedance spectrum. 18 We used two thin platinum foils as the electrodes and attached them to the top and bottom of the sample. And a layer of a mixture of Al 2 O 3 and epoxy was applied to insulate the electrode from the gasket (as shown in Fig.…”
Section: Raman Spectroscopy and Impedance Spectroscopic Measurementsmentioning
confidence: 99%
“…However, as an effective means to regulate the structure and properties of materials, pressure can better display the relationship between the structure and the properties. [17][18][19][20] For example, by compressing multiple layers of ReS 2 , Yan et al found that pressure can be used to effectively modulate the photoelectric properties of transition metal disulphide (TMDS) by controlling the atomic displacement, which has potential applications in the design and manufacture of various stacked nanoscale devices. 21 Tong et al showed that the frequency of the input signal could regulate the electric transmission operation of Bi 2 O 3 under high pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, as the phase transition approaches the Pnma phase, the narrow clearance opens (Figure b). As a result, the localized electron background becomes transparent in the gap between the Bi 3+ and O 2– ions in the color contours, indicating ionic conduction behavior. , Therefore, the O 2– ions are easily migrated in BFO. In addition, we quantify the electron density, as shown in Figure e.…”
Section: Resultsmentioning
confidence: 99%
“…In the recent past, Fluoride (F -) ion conducting batteries are under consideration as an alternative to Lithium (Li + ) ion conducting batteries due to the high theoretical energy densities of these batteries with a value of 5000 Wh/L [1]. Fluorine shows high stability due to its high electronegativity (3.98).…”
Section: Introductionmentioning
confidence: 99%
“…Fluoride ion-based electrolytes have favorable factors to provide the required energy density in batteries. Several fluoride ion conducting electrolytes such as M1-xPbxF2 (M=Ca,Sr,Ba), Pb1-xSnxF2, LaF3, BaF2 -SnF2 are reported in literature [1][2][3]. These composite solids exist in cubic fluorite structure and the conductivity is through the anti-Frenkel defect mechanism [3].…”
Section: Introductionmentioning
confidence: 99%